Mathematics Learning Performance: Its Correlation with Chemistry Learning Performance - Anchen, Cai; Ying, Zhou (Indonesian Journal of Science and Mathematics Education, 2022)
Mathematics is a rigorous, logical, and instrumental subject. Many concepts in chemistry learning is inseparable from mathematics. This study aims to determine the relationship between student learning performance in learning mathematics and chemistry. This research adopted literature analysis, statistical analysis, and interview (from subjective and objective aspects). The data of this study used the mathematics and chemistry scores of 452 students from 6 third-level grades at a secondary school in the city of Guilin. SPSS22.0 software was used to analyze comprehensive data in exploring the correlation between math scores and chemistry scores from various perspectives. Then, several students were interviewed to verify the results of the data analysis from emotional perspectives. The results of the research objectively indicate that there is a strong positive linear relationship between students’ mathematics learning achievement and subjectively, students agree that good mathematics performance can improve chemistry scores. Accordingly, mathematics learning performance is related to chemistry learning performance. Teachers can strengthen chemistry knowledge through mathematical knowledge. So, it is recommended that teachers adopt and use appropriate teaching strategies, and strengthen the application of mathematical knowledge in chemistry learning.